Scaling Kimi Delta Attention vs Full Attention: Accuracy-Throughput Trade-offs on Long-Sequence Pile Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What is the trade-off between accuracy and throughput when scaling Kimi Delta Attention (KDA) versus full attention on the Pile benchmark with sequences of 16k tokens or longer. 9 claims were extracted from source literature; 9 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.7/10. This report is a machine-generated
Machine-generated literature synthesis.